2023
DOI: 10.1007/s40948-023-00555-x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on mechanical characteristics of red sandstone under graded cyclic loading and its inspirations for stability of overlying strata

Abstract: The horizontal stress in the fractured blocks of a fractured zone is in a stress relief status under repeated mining disturbances. To investigate the effect of the horizontal stress in fractured blocks on the stability of the overlying strata, uniaxially graded cyclic loading and unloading experiments on red sandstone with different initial stress level were carried out. First, the evolution of the loading and unloading elastic modulus, irreversible strain and load-unload response ratio were analyzed. Then, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The geological structure of coal measures in China is generally complex, and the mining method is mainly underground. The proportion of the soft coal seam is as high as 82%. This kind of coal seam has the characteristics of soft and broken coal mass, low permeability, and a large gas content. In addition, with the increase of the depth of the coal seam, in situ stress, gas content, and gas pressure gradually increase .…”
Section: Introductionmentioning
confidence: 99%
“…The geological structure of coal measures in China is generally complex, and the mining method is mainly underground. The proportion of the soft coal seam is as high as 82%. This kind of coal seam has the characteristics of soft and broken coal mass, low permeability, and a large gas content. In addition, with the increase of the depth of the coal seam, in situ stress, gas content, and gas pressure gradually increase .…”
Section: Introductionmentioning
confidence: 99%
“…However, surface well extraction can disturb the overlying strata during the extraction process, and local stress field disruption can increase the surface well’s axial pressure. When the surface well is squeezed and destroyed, its extraction efficiency is significantly affected 2 , 3 . Therefore, cementing measures are necessary to enhance surface well stability and ensure efficient coalbed methane extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Coal, as one of the important fossil energy resources, is an essential resource in the industrialization and urbanization processes. In recent years, shallow resources have been gradually depleted with the growing mining intensity, and deep mining has become normal. However, deep underground mines feature great geostress and high gas concentration, so the gas content is likely to exceed the limit and gas disasters including rock and gas outbursts occur frequently. , Water injection in coal seams is one of the effective measures to control gas and has been extensively applied to coal mining. Injecting high-pressure water in coal seams through boreholes to wet and soften coal seams before mining can distribute stress uniformly, enhance the plasticity of coal, and reduce the release of elastic potential energy, thus further eliminating or decreasing the risk of coal and gas outbursts, whereas numerous research studies have shown that coal has strong hydrophobicity and deep coal seams have poor gas permeability, so water is difficult to absorb by coal seams. This may lead to waste of a huge amount of water resources and a poor water injection effect. Therefore, increasing the wettability of coal seams is the key to improving the water injection effect in the coal seams.…”
Section: Introductionmentioning
confidence: 99%